Principles and practice of oral and maxillofacial surgery : section of questions and answers - Czakó, Ladislav; Dvoranová, Bronislava (Bratislava : HERBA, 2024)
The textbook was issued on the oc- casion of 30th anniversary of the establishment of the 2nd Department of Stomatology and Maxillofacial surgery urgery of the Faculty of Medicine Comenius University in Bratislava. We aimed to update, supplement and refresh the knowledge base and facilitate under- standing major concepts of oral and maxillofacial surgery in the form of questions and multiple-choice answers. The publication is divided into a question section, an elaborative illustrations section, and an answer section. In addition to questions with the possibility of marking one or more correct answers, there is a chapter containing creative illustrations. The student or trainee has to solve problems creating a graphical representation of the solution. Correct answers and visual solutions are given in a separate chapter at the end of this publication. Any given chapter provides the possibility of self-testing of the desig nated topics in the respective field. ---------- Učebnica bola vydaná pri príležitosti 30. výročia založenia II. kliniky stomatológie a maxilofaciálnej chirurgie urgencie Lekárskej fakulty Univerzity Komenského v Bratislave. Naším cieľom bolo aktualizovať, doplniť a osviežiť vedomostnú základňu a uľahčiť pochopenie hlavných pojmov ústnej a maxilofaciálnej chirurgie formou otázok a odpovedí s možnosťou výberu z viacerých odpovedí. Publikácia je rozdelená na časť otázok, časť s podrobnými ilustráciami a časť s odpoveďami. Okrem otázok s možnosťou označenia jednej alebo viacerých správnych odpovedí je tu kapitola obsahujúca kreatívne ilustrácie. Študent alebo praktikant musí vyriešiť problémy vytvorením grafického znázornenia riešenia. Správne odpovede a vizuálne riešenia sú uvedené v samostatnej kapitole na konci tejto publikácie. Každá kapitola poskytuje možnosť samotestovania zadaných tém v príslušnej oblasti.
Bibliogr. odkazy
Keywords: chirurgia ústnej dutiny; ilustrácie lekárske; učebnica; otázky skúšobné